Efeito dos hábitos comportamentais e gordura corporal sobre indicadores de risco cardiovasculares entre adolescentes: estudo de coorte de 12 meses - Cayres, Suziane Ungari [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objectives To analyze, after 12 months, (i) the alterations in the behavioral habits and body fat under some indicators of the cardiovascular risk among adolescents, as well, (ii) if these effects of the behavioral habits and body fat were independents. In addition, from cross-sectional data were analyzed to (i) the relationship between physical activity indicators on some cardiovascular risk outcomes; (ii) the relationship between the frequency of breakfast consumption on cardiovascular risk factors, inflammatory and metabolic markers; (iii) the relationship between parasympathetic indices and resting heart rate with cardiovascular risk markers, and (iv) the relationship between hsCRP and lipid profile, blood flow and blood intima-media thickness between prepubertal adolescents were stratified according to the engagement sports practices.Methods Cohort study of 12 months, carried out in Presidente Prudente city, State of Sao Paulo. The inclusion criteria were: (i) age between 11 and 14 years old; (ii) enrolled in the school unit of elementary education; (iii) absence of any known disease; (iv) without drug consumption. All adolescents participated in each measure: (i) behavioral habits; (ii) body fat; (iii) blood pressure; (iv) heart rate resting; (v) heart rate variability; (vi) intima-media thickness; (vii) anthropometry; (viii) lipid profile; (ix) high sensitivity C reactive protein; (x) eating habits; (xi) blood flow and (xii) biological maturation. The relationship among variables were tested by correlation, and, when necessary, it were made some adjustments. Significant relationships were inserted in the multivariate model (linear regression). Teste t Student and variance analysis (ANOVA one way) established comparison among mean values. Significance statistical (p-valor) lower than 5% were considered statically different. All analyses were performed in the software BioEstat (version 5.0, Tefé, Amazonas). Results In all, 120...

Objetivos Analisar, após 12 meses de seguimento, (i) se modificações nos hábitos comportamentais e gordura corporal afetam alguns indicadores de risco cardiovasculares entre adolescentes, bem como, (ii) se estes possíveis efeitos dos hábitos comportamentais e gordura corporal foram independentes entre si. Além disso, a partir de informações transversais foram analisadas a (i) relação entre os indicadores de atividades físicas sobre alguns desfechos cardiovasculares de risco a saúde; (ii) relacionamento entre a frequência do consumo do café da manhã sobre os fatores de risco cardiovasculares, inflamatório e metabólicos; (iii) relacionamento entre índices parassimpáticos e frequência cardíaca de repouso com os marcadores de risco cardiovasculares e, (iv) relacionamento entre PCRus e o perfil lipídico, fluxo sanguíneo e EMI arterial entre adolescentes pré-puberes que foram estratificados de acordo com o engajamento de práticas esportivas. Métodos Estudo de coorte de 12 meses, realizada em Presidente Prudente/SP. Os critérios de inclusão foram: i) idade entre 11 e 14 anos; ii) estar regularmente matriculado e frequentando a unidade escolar de ensino básico; iii) não apresentar nenhum distúrbio clínico ou metabólico conhecido que impeça ou influencie na prática habitual de atividades físicas; iv) não fazer consumo eventual ou regular de medicamento que afete o controle da pressão arterial. Todos os voluntários participaram das seguintes avaliações: (i) indicadores de atividade física; (ii) gordura corporal; (iii) pressão arterial; (iv) frequência cardíaca de repouso; (v) variabilidade da frequência cardíaca; (vi) espessura médio-intimal; (vii) antropometria; (viii) perfil lipídico; (ix) proteína C reativa ultrassensível; (x) hábitos alimentares; (xi) fluxo sanguíneo e (xii) maturação biológica. O relacionamento entre as variáveis foi testado pela correlação, sendo necessário, com subsequentes...
Keywords: Sports medicine; Medicina esportiva; Sistema cardiovascular; Hábitos; Adolescentes; Tecido adiposo; Avaliação de riscos de saude; Exercícios físicos; Habitos alimentares; Pressão arterial; Variabilidade do batimento cardíaco